Broken Mirrors of Memory: Postmodernism and the Search for Meaning in Palpasa Café - Kandel, Bhanu Bhakta Sharma (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
Narayan Wagle’s novel Palpasa Café is well known among Nepali readers and has been interpreted as a travelogue or as an account of the Maoist insurgency and its impact in Nepali people, society, and the socio-political scenario of Nepal. However, rejecting linear storytelling and totalizing explanations, the novel foregrounds uncertainty, subjectivity, and multiplicity of truths through its self-reflexive narration, blurred boundary between fiction and reality, and fragmented structure. The novel destabilizes grand narratives of nationalism, revolution, and progress by exposing their contradictions and by privileging individual voices, silences, and ambiguities. Palpasa, as an elusive figure, symbolizes both absence and possibility, further intensifying the text’s play with incompleteness and deferred meaning. From a postmodern viewpoint, Palpasa Café claims that reality in the midst of war is plural, contingent, and constructed through discourse rather than fixed or absolute. The novel has opened a new avenue in Nepali literature that the truth is plural and subjective—there is no single, authoritative narrative of the Maoist conflict in Nepal. Through Drishya’s fragmented experiences, shifting voices, metafictional narration, and the blurring of fiction and reality, the novel asserts that human life under war can be understood only through personal stories, contradictions, and partial perspectives, rather than through totalizing ideologies, linear histories, or grand narratives.